Performance Enhancement of Microgrid Using Fuzzy Controller Based Reconfigurable Inverter for Solar-wind Hybrid System - M.A.Nabi; J, Surya Kumari (International Journal of Integrated Engineering, 2024)
This paper mainly concentrates on the new converter topology used for a solar hybrid energy generation for the Micro-Grid system. The Z source inverter is implemented for low distortion and low conductive losses. The reduced number components and switches are one of the main features of this circuit configuration. MATLAB simulink Simulation is performed for the new converter topology with and without fuzzy controller. This paper details to maximize the energy storage capacity with improved power quality. A single-phase inverter which is reconfigurable for a hybrid AC / DC powered grid is considered and the newly introduced single stage inverter converts the power from DC to DC and DC to AC. This inverter circuit has an advantage of reduced costs, size and losses. Using fuzzy logic based controller, the proposed inverter circuit is controlled to obtain crisp output values, thus reducing the harmonic profile by producing constant grid voltage and grid current. The inverter circuit has an impedance circuit which is not available in conventional circuits. The entire system is modelled in the MATLAB/Simulink software and the effectiveness of the system are analysed through the simulation results. The output voltage is increased with minimum sophistication using a fuzzy controller.